Early Referral to Palliative Care: The Rationing of Timely Health Care for Cancer Patients - Reis-Pina, Paulo; dos Santos, Rita Gameiro (Acta Médica Portuguesa, 2019)
Palliative care in oncology is an interdisciplinary approach, centered on patients and their families, carried out along the course of neoplastic diseases, based on symptom control, assertive communication and shared decision-making. Although clinical guidelines recommend a holistic intervention, early integration of palliative care into traditional oncological treatment, research shows a great delay in referral of patients, restricting palliative care to end-of-life care. Why does there seem to be a rationing of the early referral, sometimes in violation of human dignity? To a large extent it has to do with lack of knowledge, training and education of health professionals about palliative care and the techniques to deal with the process of death and dying. Several studies have demonstrated the benefit of integrating palliative actions into the routine of active cancer treatments, not only in terms of effective control of physical and psychological symptoms, but also in terms of overall quality of life, patient and family satisfaction, health care costs and survival in some cases. It is necessary to take measures that encourage oncologists to obtain further training in palliative care, as a formal, compulsory internship, integrated in their specific training program. This way, a new generation of physicians will surely change the lives of cancer patients, and their families, integrating — without disproportionate rationing — oncology and palliative medicine.